Exploring Seipin: From Biochemistry to Bioinformatics Predictions - Aquiles Sales Craveiro Sarmento; Lázaro Batista de Azevedo Medeiros; Lucymara Fassarella Agnez-Lima; Josivan Gomes Lima; Julliane Tamara Araújo de Melo Campos (International Journal of Cell Biology, 2018)
Seipin is a nonenzymatic protein encoded by the BSCL2 gene. It is involved in lipodystrophy and seipinopathy diseases. Named in 2001, all seipin functions are still far from being understood. Therefore, we reviewed much of the research, trying to find a pattern that could explain commonly observed features of seipin expression disorders. Likewise, this review shows how this protein seems to have tissue-specific functions. In an integrative view, we conclude by proposing a theoretical model to explain how seipin might be involved in the triacylglycerol synthesis pathway.